Blood urea nitrogen to serum albumin ratio predicts 28-day and 90-day mortality in patients with acute pancreatitis: A retrospective cohort study - Xu Cai; Xiaoqing Jiang; Wenbin Nan; Zhenyu Peng; Chenlu Wu; Kui Tang (PLoS ONE, 2025)
Background Acute pancreatitis is a prevalent and severe digestive disease with significant mortality. Early identification of high-risk patients is essential for improving outcomes. The ratio of blood urea nitrogen to albumin (BAR) has emerged as a potential prognostic predictor in various critical illnesses. This study explores the associations between BAR and 28-day and 90-day mortality in acute pancreatitis patients. Methods This retrospective cohort study enrolled patients diagnosed with acute pancreatitis from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. BAR was calculated using initial blood urea nitrogen and serum albumin. Patients were categorized into three groups according to the tertiles (T1-T3) of BAR values. Kaplan-Meier survival analysis and restricted cubic spline (RCS) curve assessed the impact of BAR on overall survival. Multivariate Cox regression analysis was used to determine association of BAR with 28-day and 90-day mortality in acute pancreatitis. The receiver operating characteristic (ROC) curve was employed to assess the predictive value of BAR for 28-day and 90-day mortality in acute pancreatitis. Results In this study, 452 patients with acute pancreatitis were analyzed, with 28-day mortality rate of 11.7% and 90-day mortality rate of 13.7%. Kaplan-Meier survival analysis indicated a notable increase in mortality rates at 28 days and 90 days among patients with elevated BAR levels (Log-rank P < 0.001). Moreover, RCS curve demonstrated a linear and positive relationship between BAR levels and mortality rates at 28 days and 90 days after adjusting all covariates. Multivariate Cox regression analysis identified BAR as an independent risk factor for 28-day and 90-day mortality. Subgroup analysis confirmed a consistent correlation between elevated BAR levels and poor outcomes in acute pancreatitis patients. The area under the curve (AUC) of BAR for predicting 28-day and 90-day mortality was 0.802 and 0.798 respectively, both performing comparably to the Simplified Acute Physiology Score II (SAPS II). Conclusion Higher BAR values were significantly associated with increased 28-day and 90-day mortality in acute pancreatitis patients. Moreover, BAR may serve as a simple and effective tool for identifying higher death risk of patients with acute pancreatitis.